Justice League [videorecording (DVD)] - Snyder, Zack, 1966-; Affleck, Ben, 1972-; Gadot, Gal, 1985-; Cavill, Henry, 1983-; Adams, Amy; Irons, Jeremy, 1948-; Lane, Diane; Nielsen, Connie, 1965-; Simmons, J. K. (Warner Bros. Entertainment, 2018)
Fueled by his restored faith in humanity and inspired by Superman's selfless act, Bruce Wayne enlists the help of his newfound ally, Diana Prince, to face an even greater enemy. Together, Batman and Wonder Woman work quickly to find and recruit a team of metahumans to stand against this newly awakened threat. But despite the formation of this unprecedented league of heroes it may already be too late to save the planet form an assault of catastrophic proportions.